PENGARUH KETERLIBATAN KONSUMEN DAN SIKAP TERHADAP KEPERCAYAAN KONSUMEN DALAM PEMANFAATAN WHATSAPP BUSINESS - Lisa Ignacia Norberta; Reza Widhar Pahlevi (Bajang Institute, 2023)
The use of social media in Indonesia is increasing. One of them is the use of the WhatsApp application. In business, WhatsApp is often used as a medium for interacting with customers. Currently, business actors are starting to use the development of the WhatsApp application called WhatsApp Business which is equipped with features that support interaction between sellers and buyers. This interaction is called the consumer engagement process. This research entitled